2021
DOI: 10.7717/peerj.11382
|View full text |Cite
|
Sign up to set email alerts
|

Predicting judging-perceiving of Myers-Briggs Type Indicator (MBTI) in online social forum

Abstract: The Myers-Briggs Type Indicator (MBTI) is a well-known personality test that assigns a personality type to a user by using four traits dichotomies. For many years, people have used MBTI as an instrument to develop self-awareness and to guide their personal decisions. Previous researches have good successes in predicting Extraversion-Introversion (E/I), Sensing-Intuition (S/N) and Thinking-Feeling (T/F) dichotomies from textual data but struggled to do so with Judging-Perceiving (J/P) dichotomy. J/P dichotomy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…The authors reported the best result for the P/J in the F1-Macro score of 80.77% for Kaggle and 65% for Kaggle-Filtered datasets. The authors suggest that the P dichotomy correlates better than the J dichotomy to linguistic markers in communication on social media [43].…”
Section: Related Workmentioning
confidence: 98%
“…The authors reported the best result for the P/J in the F1-Macro score of 80.77% for Kaggle and 65% for Kaggle-Filtered datasets. The authors suggest that the P dichotomy correlates better than the J dichotomy to linguistic markers in communication on social media [43].…”
Section: Related Workmentioning
confidence: 98%
“…Nonetheless, we are not aware of similar efforts in Latin-American countries. As per Choong and Varathan (2021) there are two approaches to personality, the trait-based approach and the typebased approach. The so-called Big Five, created by Srivastava et al (2003), is probably the best-known measurement instrument that relied on the trait-based approach that posed the idea of five large dimensions of personality, hence its name in its original English language version.…”
Section: Personality Dichotomies-mbtimentioning
confidence: 99%
“…It was created by Katherine and Isabel Briggs following Carl Jung's personality theory (Myers and Mccaulley, 1985;Myers, 1993;King and Mason, 2020). The MBTI consists of four opposite dichotomies (Myers and Myers, 2010), Extraversion-Introversion, that refers to where to focus attention and energy, introverts focus their energy inside of them and they are interested in the world of thoughts and reflections while extroverts focus their attention and energy outward, and they are interested in the world of people and things; Intuition-Sensing, that refers to what kind of information people like and trust, sensitives prefer to take information using their five senses while intuitive people go beyond what is real or concrete and focus on meaning, associations, and relationships; Feeling-Thinking, that refers to the way people make decisions, feelers make their decisions with a person-centered, values-based process while thinkers make their decisions based on impersonal, objective logic, and finally Judgment-Perceiving, that relates to the way we orient ourselves to the external world, people who prefer judgment want the external world to be organized and orderly while people who prefer perceiving, seek to experience the world, not organize it (Choong and Varathan, 2021). When combining the four dichotomies, extroversion-introversion, intuition-sensing, feeling-thinking, judgment-perceiving, it results in sixteen types of personalities (i.e.…”
Section: Personality Dichotomies-mbtimentioning
confidence: 99%
See 1 more Smart Citation
“…The MBTI is a typebased approach first developed by American psychologist Katherine Cook Briggs (1875-1968) and her psychologist daughter, Isabel Briggs Myers, based on the theory of mental types of the renowned psychoanalyst Carl G. Jung and their long-term observations and research on differences in human personality. [34,35] The MBTI serves as a reliable aid for defining personality types based on adequate research and validation, [36] including applications in career development and team building. [37,38] Structurally, the division of the MBTI into four dimensions is a natural classification method, which matches machine learning technology and is naturally friendly in terms of technical application.…”
mentioning
confidence: 99%